Red biases sex categorization of human bodies - Na Chen; Koyo Nakamura; Koyo Nakamura; Katsumi Watanabe (Frontiers in Psychology, 2023)
Color is associated with gender information (e.g., red-female). However, little has been known on the effect of color on sex recognition of human bodies. This study aimed to investigate whether the color red could influence the categorization of human bodies by sex, and the effect of contextual information. Visual stimuli were created using body silhouettes varying along the waist-to-hip ratio from female to male shapes. These stimuli were presented in conjunction with red, green, and gray colors, which were used either as body color (Experiment 1) or background color (Experiment 2). Participants were instructed to categorize the sex of the body stimuli as either male or female by pressing labeled keys. The results showed that when red was used as a body color, it induced a bias toward feminine body perception, while when used as a background color, it induced a bias toward masculine body perception. Thus, the color red influenced the sex categorization of human bodies, which being modulated by contextual information. These findings provided novel insights into the effect of contextual color cues in sex recognition of human bodies.